VP1 residues around the five-fold axis of enterovirus A71 mediate heparan sulfate interaction - Tan, C.W.; Sam, I.C.; Lee, V.S.; Wong, H.V.; Chan, Y.F. (Elsevier, 2017)
Enterovirus A71 (EV-A71) is a neurotropic enterovirus that uses heparan sulfate as an attachment receptor. The molecular determinants of EV-A71-heparan sulfate interaction are unknown. With In silico heparin docking and mutagenesis of all possible lysine residues in VP1, we identified that K162, K242 and K244 are responsible for heparin interaction and inhibition. EV-A71 mutants with K242A and K244A rapidly acquired compensatory mutations, T100K or E98A, and Q145R-T237N respectively, which restored the heparin-binding phenotype. Both VP1-98 and VP1-145 modulates heparin binding. Heparin-binding phenotype was completely abolished with VP1-E98-E145, but was restored by an E98K or E145Q substitution. During cell culture adaptation, EV-A71 rapidly acquired K98 or Q/G145 to restore the heparin-binding phenotype. Together with next-generation sequencing analysis, our results implied that EV-A71 has high genetic plasticity by modulating positively-charged residues at the five-fold axis during in vitro heparin adaptation. Our finding has impact on EV-A71 vaccine production, evolutionary studies and pathogenesis.